Adenosine triphosphate (ATP): a safe and effective vasodilator for stress perfusion cardiac magnetic resonance imaging. Issue 2 (February 2023) - Kong, H.; An, J.; Cao, J.; Tang, Z.; Tian, J.; Yong, J.; Song, X.; He, Y.
Abstract : Aim: To evaluate the efficiency and safety of adenosine triphosphate (ATP) as a stress agent in a cohort of patients undergoing stress perfusion cardiac magnetic resonance imaging (CMRI). Materials and methods: This retrospective study was conducted between December 2019 and October 2021. The study recruited patients who underwent stress perfusion CMRI using ATP as a vasodilator. Adverse events, such as chest pain, flushing, dyspnoea, headache, and splenic switch-off (SSO) phenomenon, were evaluated in the patients who underwent stress perfusion CMRI. Results: The study included 107 patients (age range: 53 ± 11 years; male:female, 62%:38%). The haemodynamic response (heart rate increased by ≥ 10 beats/min) was quick and observed within 2 minutes of ATP infusion. Scanning was stopped in three patients because of atrioventricular block. CMRI images of seven out of 104 patients were excluded from the final analysis because of inferior quality. During ATP infusion, 37/107 patients (35%) experienced mild adverse events, such as chest pain, flushing, dyspnoea, headache, and atrioventricular block. Myocardial infarction and bronchospasms were not observed during ATP infusion. SSO, a marker of adequate stress, was observed in 91% (94/103) of the patients who underwent stress perfusion CMRI. Conclusions: As a coronary vasodilator, ATP was safe for stress perfusion CMRI. In addition, the adverse events during ATP infusion were mild, which were relieved within 2 minutes of ATP injection cessation. SSO could serve as an indicator of stress success in ATP stress perfusion CMRI. Highlights: ATP is a potent coronary vasodilator that is safe for stress CMR. Splenic switch-off can serve as an indicator of stress success in ATP stress CMR. The hyperemic response to ATP is quick and comparable to adenosine reported.